Detection of isocitrate dehydrogenase 1 mutation R132H in myelodysplastic syndrome by mutation-specific antibody and direct sequencing - Andrulis, Mindaugas; Capper, David; Luft, Thomas; Hartmann, Christian; Zentgraf, Hanswalter; Deimling, Andreas von (Leukemia research, 2010)
Sequencing of the acute myeloid leukemia genome revealed somatic mutations in isocitrate dehydrogenase-1. Acute myeloid leukemia frequently develops from myelodysplastic syndrome. In order to test whether myelodysplastic syndrome also carries isocitrate dehydrogenase-1 mutations, we stained a series of bone marrow samples from patients with myelodysplastic syndrome using an antibody specific for the R132H mutation. Three out of 71 patients exhibited antibody binding to myeloid precursor cells. The presence of the R132H mutation was confirmed by DNA sequencing. We demonstrated that isocitrate dehydrogenase-1 mutations occur in myelodysplasia preceding acute myeloid leukemia and that the R132H alteration can be detected by immunohistochemistry.
Gesehen am 23.11.2022